Highly sensitive parechovirus CODEHOP PCR amplification of the complete VP1 gene for typing directly from clinical specimens and correct typing based on phylogenetic clustering. Issue 8 (3rd May 2019) - Cremer, Jeroen; Morley, Ursula; Pas, Suzan; Wolthers, Katja; Vennema, Harry; Duizer, Erwin; Benschop, Kimberley
Abstract : Purpose. Human parechoviruses (HPeVs), particularly type 3, can cause severe neurological disease and neonatal sepsis in infants. HPeV3 lacks the receptor-binding motif arginine-glycine aspartic acid (RGD), and is proposed to use a different receptor associated with severe disease. In contrast, HPeV1, which contains the RGD motif, is associated with mild disease. Rapid characterization of the presence/absence of this motif is essential for understanding their epidemiology and differential disease profiles. Current HPeV typing assays are based on partial capsid genes and often do not encompass the C-terminus where the RGD region is localized/absent. In addition, these assays lack sensitivity to enable characterization within low viral-load samples, such as cerebral spinal fluid. Methodology. We developed a highly sensitive HPeV CODEHOP PCR, which enables typing of parechoviruses directly from clinical samples while generating a complete VP1 gene, including the C-terminus. Results. The assay was HPeV-specific and has a sensitivity of 6.3 TCID50 ml −1 for HPeV1 and 0.63 TCID50 ml −1 for HPeV3. Analysis of the complete VP1 gene in comparison to partial VP1 fragments generated by previously published PCRs showed homologous clustering for most types. However, phylogenetic analysis of partial VP1 fragments showed incongruent typing based on the 75 % homology classification rule. In particular, the strains designated as type 17 were found to be either type 3 or 4 when using the (near-) complete VP1 fragment. Conclusion. While enabling sensitive characterization of HPeVs directly from clinical samples, the HPeV CODEHOP PCR enables the characterization of RGD and non-RGD strains and correct HPeV typing based on the complete VP1.